2005
DOI: 10.4049/jimmunol.174.2.1104
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Novel Orphan, C5a Receptor (C5L2), during Experimental Sepsis and Sepsis in Humans

Abstract: Sepsis is associated with extensive complement activation, compromising innate immune defenses, especially in neutrophils (PMN). Recently, a second C5a receptor (C5L2) was detected on PMN without evidence of intracellular signaling. The current study was designed to determine changes in C5L2 in blood PMN during sepsis. In vitro exposure of PMN to C5a, but not to fMLP, led to reduced content of C5L2. Following cecal ligation and puncture-induced sepsis in rats, PMN demonstrated a time-dependent decrease in C5L2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 48 publications
2
64
0
Order By: Relevance
“…Moreover, C5L2 −/− mice show marginal improvement of survival in Escherichia coliinduced sepsis [29]. In contrast, the expression levels of C5L2 are reduced in neutrophils from rats and humans with progressive sepsis, which is associated with poor prognosis [30]. Thus, the functional roles of C5L2 have still been controversial in sepsis [31].…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, C5L2 −/− mice show marginal improvement of survival in Escherichia coliinduced sepsis [29]. In contrast, the expression levels of C5L2 are reduced in neutrophils from rats and humans with progressive sepsis, which is associated with poor prognosis [30]. Thus, the functional roles of C5L2 have still been controversial in sepsis [31].…”
Section: Discussionmentioning
confidence: 98%
“…[9][10][11][12] ). Furthermore, in human sepsis, C5L2 is downregulated on the surfaces of PMNs, the extent of which correlates with the harmful outcomes of sepsis 15 .…”
Section: Discussionmentioning
confidence: 99%
“…After washing of the 'buffy coat', we incubated PBMCs (3.5 × 10 6 cells/ml) with recombinant human C5A (50 nM; R&D Systems) for 12 × h at 37 °C in OPTI-MEM I. We isolated human PMNs as described elsewhere 15 and incubated them (5 × 10 6 cells/ml) for 5 h under the same conditions described above. As indicated in Figure 5, we pre-exposed PMNs and PBMCs to monoclonal antibodies to human C5AR 19 or C5L2 (1 μg/ml) or to A8 Δ71-73 (350 nM) 1 h before C5A exposure (50 nM) 17 .…”
Section: In Vitro Incubation Of Phagocytic Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, C5aR and C5L2 are independent, and the putative 'default' receptor, C5L2, has an important role in balancing the biological effects of C5a. 6 However, the role of C5L2 in inflammatory responses is controversial, 7,8 its elucidation will require further investigation. In sepsis, it has been reported that excessive systemic C5a levels were associated with exhaustion of the granulocytic response.…”
Section: Introductionmentioning
confidence: 99%